2018
DOI: 10.4317/jced.54186
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sealing ability of endodontic cements apical plugs

Abstract: BackgroundIt is unknown whether the bioactivity of Biodentine characterized by the precipitation of hydroxyapatite and formation of tags into the dentinal tubules improve its sealing ability as an apical plug. Aim: To evaluate the sealing ability provided by Biodentine and mineral trioxide aggregate (MTA) apical plugs, with or without phosphate-buffered saline (PBS) intracanal dressing, using a glucose leakage method.Material and MethodsThe space of the canal of 100 root segments with about 12 mm long was shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Nevertheless, the values of infiltration were significantly lower than the positive control, thus corroborating the fact that MTA have suitable sealing ability. This is in agreement with previous studies that state that the incidence of leakage in MTA apical plug is related to the presence of failures within the sealer, at the sealer-dentin interface, and/or by the presence of pores [56].…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the values of infiltration were significantly lower than the positive control, thus corroborating the fact that MTA have suitable sealing ability. This is in agreement with previous studies that state that the incidence of leakage in MTA apical plug is related to the presence of failures within the sealer, at the sealer-dentin interface, and/or by the presence of pores [56].…”
Section: Discussionsupporting
confidence: 93%
“… 23 Similar to MTA, its bioactivity has been evidenced by the precipitation of hydroxyapatite and the formation of tags that penetrate the dentinal tubules. 26 Biodentine is comparable to MTA except for zirconium oxide being added to its powder component. The larger particle size, incorporation of calcium chloride to the liquid constituent, and reducing the overall liquid component contributes to a decreased setting time approximating 12 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…In studies by Ayatollahi et al 27 and Nabavizadeh et al, 28 Peeso Reamer drills were used to simulate open apex conditions. Cechella et al 26 created a standardized open apex using the #6 Gates-Glidden drill. In the present study, root end preparation was done using a bur as in the study by Kim et al 29 to simulate an open apex with thin dentinal walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 6 and 12 month long observation periods, Biodentine™ showed better root apex closing properties and dentine thickness than MTA [44]. Moreover, it was found that Biodentine™ at 4 mm thickness applied in the apical area of the root shows good impermeability, though less than that of MTA [45,46]. Revitalization procedures, being a part of regenerative endodontics, became an alternative to apexification in immature teeth after pulp necrosis.…”
Section: The Use Of Biodentine™ In Apexification and Regeneretive Endmentioning
confidence: 99%